2005
DOI: 10.1086/426447
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Toxoplasma Infection by Molecular Monitoring of Toxoplasma gondii in Peripheral Blood Samples after Allogeneic Stem Cell Transplantation

Abstract: Toxoplasmosis occurs more commonly after HSCT than has previously been suggested, and routine PCR testing of peripheral blood specimens may be an appropriate tool for guiding preemptive therapy in patients at very high risk of developing invasive disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
240
2
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(258 citation statements)
references
References 40 publications
14
240
2
2
Order By: Relevance
“…Most cases of toxoplasmosis after HSCT are only diagnosed at autopsy because histological evidence of organ involvement is rarely obtained before death 6 . The early detection of T. gondii DNA in body fluids by PCR methods has been considered an important tool for monitoring Toxoplasma infection following HSCT 5,6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cases of toxoplasmosis after HSCT are only diagnosed at autopsy because histological evidence of organ involvement is rarely obtained before death 6 . The early detection of T. gondii DNA in body fluids by PCR methods has been considered an important tool for monitoring Toxoplasma infection following HSCT 5,6 .…”
Section: Discussionmentioning
confidence: 99%
“…The early detection of T. gondii DNA in body fluids by PCR methods has been considered an important tool for monitoring Toxoplasma infection following HSCT 5,6 . A recent study has shown the importance of monitoring toxoplasmosis after HSCT with biological tests that combine PCR and serological techniques 3 .…”
Section: Discussionmentioning
confidence: 99%
“…It is higher in areas of endemicity, ranging from 6% in Europe [5,6] and 3% in Brazil [7] compared to 50.5% in USA [3,4] or Japan [8]. In one prospective study of seropositive allo-SCT recipients, 16% reactivated the infection over the first 6 months after transplant and 6% developed disease [6].…”
Section: Commentarymentioning
confidence: 99%
“…It is higher in areas of endemicity, ranging from 6% in Europe [5,6] and 3% in Brazil [7] compared to 50.5% in USA [3,4] or Japan [8]. In one prospective study of seropositive allo-SCT recipients, 16% reactivated the infection over the first 6 months after transplant and 6% developed disease [6]. As discussed by Cavattoni et al [1], diagnosis can be difficult due to the protean presentations of disease: with fever of unknown origin, neurological symptoms, pneumonitis, or myocarditis as well as disseminated infection with multisystem failure.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation